A DEMATEL-AISM analysis for the longevity of prefabricated building under low carbon emission - Yu-Xin Wu; Ming-Kun Li; Xin-Yue Gao (Journal of Asian Architecture and Building Engineering)
Prefabricated buildings (PBs) possess a unique potential for energy conservation and pollution mitigation. Extending the lifespan of PBs can reduce cost-effectiveness and improve operational efficiency in the construction industry. This study formulates a comprehensive supply chain model encompassing the whole life cycle of PBs and delineates the factors influencing carbon emissions and service longevity at each stage. Decision-making trial and evaluation laboratory (DEMATEL) and analytic interference structure model (AISM) methodologies are integrated into the modeling process, helping to amplify the clarity of logical interconnections among the factors. Within this framework, an UP/DOWN topology relationship diagram is used to prove the third-order and fourth-level correlations between these factors. The findings of this research pinpoint two distinct optimization pathways within prefabricated building supply chains (PBSCs), shaped by 10 critical factors, including government incentives, corporate social responsibility, building operational energy consumption, demolition programs and procedures, and prefabrication rates. Furthermore, the research shows that governmental and commercial sectors have a key influence in regulating low-carbon strategies across the PBs life cycle. These findings provide a valuable reference for improving future construction projects, promoting energy efficiency, and driving emission reductions in the industry.